Incidence and disease spectrum of inherited metabolic diseases screened by tandem mass spectrometry in Huai'an from 2018 to 2024 - Ou, Ming-ming; Sun, Chun-tao; Zhang, Li; Kong, Ling-li; Zhang, Lin-xin; Zheng, Jun; Zhang, Pei-ying; Wang, Yu-mei; Lin, Xiao-fei; Yang, Xin (Frontiers in Pediatrics, 2025)
ObjectivesThis study aimed to determine the incidence and disease spectrum of inherited metabolic diseases (IMDs) among newborns in Huai'an City, China.MethodsExpanded newborn screening for IMDs using tandem mass spectrometry (MS/MS) enables the simultaneous analysis of more than 40 metabolites and the identification of approximately 50 types of IMDs. Next-generation sequencing (NGS), targeting hundreds of IMD-associated genes, was subsequently performed for genetic analysis of patients identified through screening. Between June 2018 and December 2024, in total, 161,966 newborns in Huai'an were screened using MS/MS. Ultimately, 57 patients were diagnosed with IMDs based on plasma amino acid and acylcarnitine profiling, urinary organic acid analysis, and molecular genetic testing, performed via NGS. Data were analyzed using descriptive statistics.ResultsFifty-seven cases of IMDs were diagnosed, corresponding to an overall incidence rate of 1 in 2,842. Among these, 28 cases involved amino acid metabolism disorders (1 in 5,785), 17 cases of organic acid metabolism disorders (1 in 9,527), and 12 cases of fatty acid oxidation disorders (1 in 13,497). The three most common IMDs were phenylalanine hydroxylase deficiency (1 in 8,098), primary carnitine deficiency (1 in 23,138), and methylmalonic acidemia (1 in 32,393). Genetic testing revealed variants in all 57 patients, with 75 variants identified across 17 IMD-associated genes. Recurrent variants were observed in five IMDs, including PAH gene variants c.728G>A, c.611A>G, and c.721C>T for phenylketonuria, PAH c.158G>A, c.721C>T, and c.728G>A for mild hyperphenylalaninemia, SLC22A5 c.1400C>G for primary carnitine deficiency, MMACHC c.609G>A, c.567dup and c.482G>A for methylmalonic acidemia, ACADS c.1055C>T, and c.1130C>T for short-chain acyl-CoA dehydrogenase deficiency, and ACADSB c.923G>A for 2-methylbutyrylglycinuria. All these recurrent variants were reported as pathogenic or likely pathogenic, except PAH c.158G>A, which was classified as a variant of uncertain significance.ConclusionThe majority of IMD patients in Huai'an carried pathogenic or potentially pathogenic variants identified through expanded newborn screening. Although MS/MS newborn screening followed by NGS confirmation cannot prevent the occurrence of IMDs, timely diagnosis combined with appropriate treatment and management can effectively prevent morbidity, reduce mortality, and support long-term symptom control. Overall, this study demonstrates that MS/MS-based newborn screening combined with molecular diagnosis was highly effective for the study early detection and management of IMDs in the Huai'an population.